A Review of Blockchain Technology Adoption in the Tourism Industry from a Sustainability Perspective - Prados-Castillo, Juan F.; Guaita Martínez, José Manuel; Zielińska, Agnieszka; Gorgues Comas, Dolores (Journal of theoretical and applied electronic commerce research, 2023)
The deployment of Blockchain technology in the tourism industry is already becoming a reality with the gradual emergence of innovative business models. At its core is the promise of improving the efficiency of the tourism service value chain and enhancing the quality of the service provided to the end customer. This paper analyses research trends focused on using Blockchain technology in tourism. The aim is to determine how this technology impacts the tourism sector and its sustainability. A systematic review, descriptive bibliometric analysis, and network analysis based on co-authorship, co-citation, and keyword analysis criteria, among others, have been used. The results reveal that the subject matter analysed is generating a growing trend in academic research in the fields of sustainable management and supply chain efficiency. The activities in the tourism sector that are incorporating this technology to a greater extent are those related to the areas of marketing, logistics, and smart business models, according to the data extracted from the analysis. This technology already enables the application of solutions that predict and promote tourist behaviour based on sustainable behaviour and consumption habits, generating value for the different stakeholders.